The use of pediatric locked plates in the paralytic hip: preliminary results of 61 cases - Frederico Coutinho de Moura Vallim; Henrique Abreu da Cruz; Ricardo Carneiro Rodrigues; Caroline Sandra Gomes de Abreu; Eduardo Duarte Pinto Godoy; Marcio Garcia Cunha (Revista Brasileira de Ortopedia)
ABSTRACT Objective: To evaluate the clinical and radiologic results of proximal femoral varus derotational and shortening osteotomy (OVRF) (Port., doesn't match name) with the use of a locked plate in patients with cerebral palsy, classified by the gross motor functional classification system as class IV or V. Methods: A retrospective study of 42 patients (61 hips) with cereFbral palsy, gross motor functional classification system class IV or V, submitted to OVRF. The minimal follow up was 24 months. This study evaluated clinical (age at surgery, gender, Gross Motor Functional Classification System class, anatomical cerebral palsy classification, and motor pattern), pre- and post-operative radiological (neck shaft angle, acetabular index, Reimers migration index and time until bone healing) characteristics, as well as post-operative complications. Results: Mean pre-operative cervicodiaphyseal angle, acetabular index, and Reimers migration index were respectively 121.6°, 22.7°, and 65.4% in uncomplicated cases, and 154.7°, 20.4°, and 81.1% in complicated ones. All parameters were statistically significant difference between pre- and postoperative values (p < 0.05). The patients with postoperative complications had a greater cervicodiaphyseal angle and Reimers migration index (p < 0.0001). There were no differences in clinical characteristics, time of immobilization, or bone healing. Fourteen patients had postoperative complications (33.3%), but only six required surgical treatment. Conclusion: The locked plate is a safe resource, with low complication rates and reproducible technique for OVRF in the cerebral palsy population classified as gross motor functional classification system IV and V. Greater cervicodiaphyseal angles and Reimers migration index are associated with greater chances of postoperative complications, as well as gross motor functional classification system V classification.